THE RELATIONSHIP BETWEEN SYNTAX AND POETIC RHYTHM - Yunusova Muattar Shakirovna (International Journal of Literature and Language Studies, 2026)
This article explores the interrelationship between syntax and poetic rhythm in literary texts, focusing on how syntactic structures contribute to the formation of rhythm in poetry. The study examines the ways in which word order, sentence length, grammatical inversion, and structural parallelism influence rhythmic patterns in poetic discourse. Drawing on linguistic and stylistic approaches, the paper argues that poetic rhythm is not solely a phonological phenomenon but also a syntactic construct shaped by the arrangement of linguistic units. The analysis demonstrates that syntax plays a crucial role in creating aesthetic effects, emphasizing meaning, and guiding emotional perception in poetry. The findings suggest that poets intentionally manipulate syntactic structures to achieve rhythmical balance, tension, and expressive depth.